Anhydridization method of anhydride cured epoxy resin degradation product
Through steps such as acidification, dehydration and reduced pressure distillation, the degradation products of epoxy resin are converted into acid anhydride products, which solves the problems of waste of resources and high production costs in the prior art, and realizes efficient recycling and reuse of epoxy resin.
Patent Information
- Application Number
- CN202411477537.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively use acid anhydride to cure epoxy resin degradation products, resulting in waste of resources and high production costs.
By an acid anhydride method, the dicarboxylate salt in the degradation product of the epoxy resin is acidified, dehydrated and distilled under reduced pressure to obtain an acid anhydride product, which is used to prepare a new epoxy resin insulating material.
It realizes efficient recycling and reuse of epoxy thermosetting plastics, reduces resource waste and production costs, and improves the economic benefits of the anhydride curing system.
Smart Images

Figure CN119431289A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of epoxy resin material recycling, in particular to a method for anhydriding anhydride-cured epoxy resin degradation products. Background Art
[0002] After curing, epoxy resin can form a highly cross-linked three-dimensional network structure with excellent electrical and mechanical properties. Therefore, it is widely used in cast insulation of electrical equipment such as dry-type transformers, voltage transformers and composite insulators. After the retirement of electrical equipment, due to the particularity of the structure, the only way to recycle the metal components in epoxy resin solid insulation is by chemical degradation.
[0003] At present, the recycling method of anhydride cured epoxy resin degradation products is basically to add new epoxy monomers and curing agents for re-curing. Due to the lack of active functional groups, the degradation products are generally difficult to be used as additives or catalysts to prepare new epoxy resin materials. Even if some active groups such as ester groups and hydroxyl groups are introduced into the degradation products obtained by alcoholysis, the performance of the regenerated epoxy thermosetting plastic is relatively poor. At present, there is almost no method for targeted functional group repair of the main component dicarboxylate in the alcoholysis product and efficient reuse. The traditional anhydride production method is relatively backward, with high cost, serious equipment corrosion, and environmental pollution caused by waste liquid. Summary of the invention
[0004] In order to solve the above problems, the present invention proposes a method for anhydriding anhydride-cured epoxy resin degradation products, and the specific technical scheme is as follows: A method for anhydriding an anhydride-cured epoxy resin degradation product, comprising the following steps: Step 1: Degrading the epoxy resin with a degradation solution to obtain a degradation mixture, and separating the degradation mixture to obtain a dicarboxylate; Step 2: acidifying the dicarboxylate with a hydrochloric acid solution, and removing water by rotary evaporation to obtain a solid residue; Step 3: dissolving the solid residue in ethanol, filtering to remove salt, and removing ethanol from the filtrate by rotary evaporation and drying to obtain a dicarboxylic acid; Step 4: Mix and heat the dicarboxylic acid, alkali metal salt or alkaline earth metal salt, and water-carrying agent to dehydrate the dicarboxylic acid to obtain a mixture containing anhydride; Step 5: distill the mixture containing the acid anhydride under reduced pressure for the first time to remove the solvent, then heat it up to distill under reduced pressure for the second time, collect the obtained fractions, and obtain the acid anhydride product.
[0005] Furthermore, the alkali metal salt is sodium dihydrogen phosphate or disodium hydrogen phosphate; and the alkaline earth metal salt is barium hydroxide or magnesium oxide.
[0006] Furthermore, the mass fraction of the hydrochloric acid solution used is 15-20wt.%, the reflux temperature is 70-90°C, and the time is 1-3h.
[0007] Furthermore, in step 4, the heating temperature is 180-210° C., and the reaction time is 3-6 hours.
[0008] Furthermore, in step 5, the temperature of the first reduced pressure distillation is 70-85° C. and the pressure is 300-500 Pa.
[0009] Furthermore, in step 5, the temperature of the second reduced pressure distillation is 95-110° C. and the pressure is 300-500 Pa.
[0010] Furthermore, the degradation liquid is prepared by mixing ethylene glycol and sodium hydroxide in a mass ratio of 15 to 30:1.
[0011] Furthermore, the epoxy resin in step 1 is degraded in a sealed container at a degradation temperature of 150°C.
[0012] Furthermore, the dicarboxylate is obtained by separating the degradation mixture through precipitation.
[0013] Furthermore, the epoxy resin is prepared with a bisphenol A epoxy resin matrix, methyltetrahydrophthalic anhydride as a curing agent and 2,4,6-tris(dimethylaminomethyl)phenol as a catalyst.
[0014] Beneficial effects: The present invention can be used for degradation and recycling through a simple and efficient alkali / alcohol system, and a degradation product containing multiple hydroxyl groups or carboxyl groups is obtained through alkali-catalyzed degradation of epoxy thermosetting plastics. The degradation product containing carboxyl groups can be efficiently converted into anhydride curing agents, and the regenerated anhydride curing agent monomers can be used to prepare new epoxy resin insulating materials, thereby realizing closed-loop recycling, effectively saving resources, and reducing production costs. A solution is provided for the problems of low effective utilization rate and poor economic benefits of epoxy material degradation and recycling products under a traditional anhydride curing system, and resources can be effectively saved. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a diagram showing the infrared spectrum characterization results of the anhydride products of Examples 1, 2, and 3 of the present invention. DETAILED DESCRIPTION
[0016] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. For the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0017] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0018] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0019] A method for anhydriding an anhydride-cured epoxy resin degradation product, comprising the following steps: Step 1: Degrading the epoxy resin with a degradation liquid to obtain a degradation mixture, and separating the degradation mixture to obtain a dicarboxylate.
[0020] The epoxy resin is prepared with a bisphenol A epoxy resin matrix, methyltetrahydrophthalic anhydride (MTHPA) as a curing agent and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30) as a catalyst. The epoxy resin is degraded in a sealed container at a degradation temperature of 150°C. The degradation liquid is prepared by mixing ethylene glycol and sodium hydroxide in a mass ratio of 15 to 30:1.
[0021] Step 2: The dicarboxylate is acidified with hydrochloric acid solution and refluxed, and most of the water is removed by rotary evaporation to obtain a solid residue.
[0022] The mass fraction of the hydrochloric acid solution used is 15-20wt.%, the reflux temperature is 70-90°C, and the reflux time is 1-3h.
[0023] Step 3: The solid residue is dissolved in ethanol, filtered to remove salt, and the filtrate is subjected to rotary evaporation to remove ethanol and dried to obtain a dicarboxylic acid.
[0024] Step 4: Mix and heat the dicarboxylic acid, alkali metal salt or alkaline earth metal salt and water-carrying agent to dehydrate the dicarboxylic acid to obtain a mixture containing anhydride.
[0025] Wherein, the alkali metal salt is sodium dihydrogen phosphate or disodium hydrogen phosphate; the alkaline earth metal salt is barium hydroxide or magnesium oxide; the heating temperature is 180-210° C., and the reaction time is 3-6 hours.
[0026] Step 5: distill the mixture containing the acid anhydride under reduced pressure for the first time, and after the solvent is completely evaporated, increase the temperature to distill under reduced pressure for the second time, collect the obtained fractions, and obtain the acid anhydride product.
[0027] The temperature of the first vacuum distillation is 70-85°C, the temperature of the second vacuum distillation is 95-110°C, and the pressure is 300-500Pa.
[0028] like Figure 1 As shown, the mechanism of anhydride reaction of epoxy resin degradation products is: (1) Dicarboxylates generate dicarboxylic acids under the action of hydrochloric acid. Since hydrochloric acid is a relatively strong acid, its degree of ionization in aqueous solution is greater than that of dicarboxylic acids. The hydrogen ions generated by ionization can combine with the acid radical ions of dicarboxylates to form weaker acid molecules that are more difficult to ionize and "free" from the system, thereby causing the chemical equilibrium to move toward the formation of dicarboxylic acids. The reaction process is as follows:
[0029] (2) When dicarboxylic acids are heated at high temperatures, they undergo a dehydration reaction catalyzed by alkali metal or alkaline earth metal salts. The water-carrying agent quickly removes the generated water from the reaction system, causing the reaction to move in the forward direction, resulting in dicarboxylic anhydride.
[0030]
[0031] In one embodiment, the dicarboxylate salt is obtained by separating the degradation mixture by precipitation.
[0032] Specifically, ethanol is added to the degradation mixture to generate precipitation, and the precipitate is filtered, and the obtained precipitate is the dicarboxylate.
[0033] The specific embodiments are as follows: Embodiment 1: (1) Preparation of epoxy resin Weigh 23g of E-51 resin and add it to a container containing a magnet, then weigh 16.2g of curing agent methyltetrahydrophthalic anhydride (MTHPA) and add it to the container, and stir MTHPA and E-51 resin at 80°C for 20 minutes to make them evenly mixed, wherein the stirring speed is 200rpm. The mixed solution is vacuum degassed in a vacuum drying oven at a temperature of 80°C for 30 minutes; after the vacuum degassed, add 0.24g of catalyst 2,4,6-tris(dimethylaminomethyl)phenol to the mixed solution, and stir again at a constant temperature of 60°C for 20 minutes to mix evenly to obtain a resin prepolymer glue. Subsequently, vacuum degassing was carried out in a vacuum drying oven at 80°C for 30 min, and the degassed resin prepolymer glue was poured into a stainless steel mold preheated at 120°C and coated with a release agent. It was first cured at 120°C for 2 h and then at 150°C for 4 h. After natural cooling and demolding, the epoxy resin was prepared.
[0034] (2) Epoxy resin degradation 3 g of the epoxy resin prepared above was weighed and placed in a degradation container, and 20 mL of degradation solution was added to the container, wherein the degradation solution was prepared by ethylene glycol and sodium hydroxide at a mass ratio of 25:1, and the mass ratio of epoxy resin to ethylene glycol and sodium hydroxide was 3:25:1. The container was then sealed and placed in a 150°C constant temperature drying oven, and allowed to stand for degradation for 6 hours to finally obtain a degradation mixture, which was precipitated and separated to obtain a dicarboxylate.
[0035] (3) Preparation of dicarboxylic acids Weigh 1.2 g (about 6.5 mmol) of the degradation product dicarboxylate in a round-bottom flask, add 10 mL of 18 wt.% HCl solution, and reflux at 80 °C for 2 h. Then remove most of the water by rotary evaporation, dissolve the residue in 15 mL of ethanol, and remove the salt by filtration. The filtrate is rotary evaporated to remove ethanol and dried in a constant temperature drying oven at 80 °C for 24 h to obtain dicarboxylic acid.
[0036] (4) Anhydration of dicarboxylic acids Weigh 5g of dicarboxylic acid and add it to a three-necked flask with a magnet, a thermometer, a spherical condenser, and a water separator, add 0.1g of catalyst magnesium oxide (MgO), and then weigh 10g of water-carrying tetralin and add it to the three-necked flask to mix with it. Then put the three-necked flask into a 200℃ oil bath, stir and heat to react for 4h. After the reaction is completed, first distill the solvent out of the reaction system at 85℃ and 300Pa, collect the reaction solvent, and the obtained reaction solvent can be reused; after the solvent is completely evaporated, heat it to 100℃ and distill it under reduced pressure again, collect the obtained fraction, and obtain the anhydride product. The conversion rate of the obtained product is 93.6%, and the purity of the product is 97.5%.
[0037] Embodiment 2: Based on step (4) of Example 1, the catalyst magnesium oxide was replaced with barium hydroxide Ba(OH)2, and the anhydride product was generated according to the above steps. The conversion rate of the obtained product was 92.1%, and the purity of the product was 97.6%.
[0038] Embodiment 3: Based on step (4) of Example 1, the catalyst magnesium oxide was replaced with sodium dihydrogen phosphate NaH2PO4, and the anhydride product was generated according to the above steps. The conversion rate of the obtained product was 63.1%, and the purity of the product was 97.6%.
[0039] Embodiment 4: Based on step (4) of Example 1, the catalyst magnesium oxide was replaced with disodium hydrogen phosphate Na2HPO4, and the anhydride product was generated according to the above steps. The conversion rate of the obtained product was 57.6%, and the purity of the product was 97.3%.
[0040] like Figure 1 As shown in the FTIR spectrum of the synthesis results, it can be seen that the wave number is 3500cm -1 The hydroxyl peak of phthalic acid disappears at 1852 cm -1 CO asymmetric stretch at 1764 cm -1 The CO symmetric stretch at 1257 cm -1 The CO stretch at , indicating that the anhydride was successfully synthesized.
[0041] The results show that the type of catalyst has a great influence on the yield of the product dibasic anhydride. Among the catalysts investigated, the catalytic activity of alkaline earth metal salts is significantly higher than that of alkali metal salts, among which magnesium oxide (MgO) has the best catalytic activity, and the conversion rate of the obtained product is 93.6%.
[0042] The effect of the amount of water-carrying agent on the results of the acid anhydride synthesis reaction was tested. The amount of magnesium oxide was 0.1 g, and other conditions were kept constant to investigate the effect of the amount of water-carrying agent on the reaction results. The results are shown in Table 1.
[0043] Table 1 Effect of the amount of water-carrying agent on the results of anhydride synthesis reaction
[0044] As can be seen from Table 1, the amount of water-carrying agent also has a certain effect on the reaction. When the amount of water-carrying agent is less, the conversion rate of the product obtained by the reaction is low, because the less water-carrying agent makes it difficult for the reactants to react evenly. As the amount of water-carrying agent increases, the product conversion rate continues to increase; when the amount of water-carrying agent is greater than 10g, the product conversion rate is the highest, reaching 93.6%; when the amount of water-carrying agent is increased, the product yield decreases slightly, because the increase in the amount of water-carrying agent dilutes the catalyst concentration, which is not conducive to the reaction. Therefore, the amount of water-carrying agent is preferably 10g.
[0045] Therefore, through multiple experimental explorations, when using alkaline earth metal catalyst magnesium oxide, the conversion rate of the obtained anhydride product is the highest, which is 93.6%. The present invention realizes the full utilization of the degradation products of waste epoxy thermosetting plastics and effectively solves the waste of resources.
[0046] It should be noted that all raw materials used in the examples of the present invention were purchased from commercial sources, and the instruments used were conventional laboratory equipment.
[0047] The reagents and instruments used in the present invention are as follows: Reagents used in the present invention:
[0048] Instruments used in the present invention:
[0049] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for anhydriding an anhydride-cured epoxy resin degradation product, characterized in that: The following steps are involved: Step 1: Degrading the epoxy resin with a degradation liquid to obtain a degradation mixture, and separating the degradation mixture to obtain a dicarboxylate; Step 2: Acidify the dicarboxylate with a hydrochloric acid solution, and remove water by rotary evaporation to obtain a solid residue; Step 3: dissolving the solid residue in ethanol, filtering to remove salt, and removing ethanol from the filtrate by rotary evaporation and drying to obtain a dicarboxylic acid; Step 4: Mix and heat the dicarboxylic acid, alkali metal salt or alkaline earth metal salt, and water-carrying agent to dehydrate the dicarboxylic acid to obtain a mixture containing anhydride; Step 5: distill the mixture containing the acid anhydride under reduced pressure for the first time to remove the solvent, then heat it up to distill under reduced pressure for the second time, collect the obtained fractions, and obtain the acid anhydride product.
2. The method according to claim 1, characterized in that The alkali metal salt is sodium dihydrogen phosphate or disodium hydrogen phosphate; the alkaline earth metal salt is barium hydroxide or magnesium oxide.
3. The method according to claim 1, characterized in that: The mass fraction of the hydrochloric acid solution used is 15~20wt.%, the reflux temperature is 70~90℃, and the time is 1~3h.
4. The method according to claim 1, characterized in that: In step 4, the heating temperature is 180-210° C. and the reaction time is 3-6 h.
5. The method according to claim 1, characterized in that The temperature of the first reduced pressure distillation in step 5 is 70-85° C. and the pressure is 300-500 Pa.
6. The method according to claim 1, characterized in that The temperature of the second reduced pressure distillation in step 5 is 95-110° C. and the pressure is 300-500 Pa.
7. The method according to claim 1, characterized in that The degradation liquid is prepared by mixing ethylene glycol and sodium hydroxide in a mass ratio of 15 to 30:
1.
8. The method according to claim 7, characterized in that The epoxy resin in step 1 is degraded in a sealed container at a degradation temperature of 150°C.
9. The method according to claim 1, characterized in that: The dicarboxylate salt is obtained by separating the degradation mixture by precipitation.
10. The method according to claim 1, characterized in that The epoxy resin is prepared with bisphenol A epoxy resin as a matrix, methyltetrahydrophthalic anhydride as a curing agent and 2,4,6-tris(dimethylaminomethyl)phenol as a catalyst.